Effects of condensed tannins from Leucaena on methane reduction, rumen fermentation and populations of methaogens and protozoa in vitro - Tan, Hui Yin (Elsevier, 2011)
Different levels of purified condensed tannins (CT) extracted from Leucaena leucocephala hybrid-Rendang (LLR) were investigated for their effects on CH4 production, rumen fermentation parameters such as pH, dry matter (DM) degradability, N disappearance and volatile fatty acid (VFA) concentrations, as well as on populations of rumen methanogenic archaea and protozoa in vitro. Purified CT concentrations of 0 (control), 10, 15, 20, 25 and 30 mg, and 500 mg of oven dried guinea grass (Panicum maximum) with 40 ml of buffered rumen fluid were incubated for 24 h using an in vitro gas production procedure. Total gas (ml/g DM) decreased at a decreasing rate (linear P < 0.01; quadratic P < 0.05) with increased levels of CT inclusion. CH4 production (ml/g DM) decreased at a decreasing rate (linear P < 0.01; quadratic P < 0.01) with increasing levels of CT. Total VFA concentration (mmol/L) decreased at a decreasing rate (linear P < 0.01; quadratic P < 0.01) with increasing CT inclusions. In vitro DM degradation and N disappearance declined linearly (P < 0.01) with increasing levels of CT. Estimates of rumen methanogenic archaea and protozoa populations using microbiological methods and real-time PCR assay showed linear reductions in total methanogens (P < 0.01) and total protozoa (P < 0.01) with increasing levels of CT. Methanogens in the order Methanobacteriales also declined, but with quadratic and cubic aspects. Results suggest that CT from LLR at a relatively low level of 15 mg of CT/500 mg DM reduce CH4 production by 47%, with only 7% reduction in degradation of feed DM. However, higher CT inclusions, while further reducing CH4 emissions, have substantive negative effects on DM digestibility.